Strain response and damage modelling of glass/epoxy pipes under various stress ratios. (November 2014) - Abdul Majid, M. S.; Gibson, A. G.; Hekman, M.; Afendi, M.; Amin, N. A. M.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents the stress–strain response and general lifetime damage modelling of glass fibre reinforced epoxy (GRE) composite pipes subjected to multi-ratios stress loadings at room temperature (RT). This particular modelling work was developed to predict the non-linear stress–strain response caused by the fatigue static and cyclic loading in the multiaxial ultimate elastic wall stress (UEWS) tests by considering the effects of matrix cracking within the laminates. Although the UEWS procedure is not a standard protocol used for qualification of GRE pipes, it appears to offer an option to existing procedures delineated in ASTM D2992. The ply properties initially expressed as a function of crack density was computed as a function of increasing stress and strain using shear lag approximation. In general lifetime damage model, the effects of stress developed in each ply from ultimate elastic wall stress (UEWS) test were expressed in a single quadratic term of axial and hoop stress. The term then solved to produce limits with respect to axial and hoop stress, which represented in a graphical form of failure envelope. The predictions from both models are found to be in good agreement with the data from the multiaxial UEWS tests of ±55° filament wound GRE pipes. These models thus enable for the long term performance prediction of the pipes under combined loadings.